ASSESSMENT OF OPERATION THEATRE STAFF KNOWLEDGE, ATTITUDE, AND PRACTICES REGARDING THE PREPARATION OF COVID-19 POSITIVE PATIENTS FOR SURGICAL PROCEDURE: A CROSS-SECTIONAL SURVEY - GUL, A; ISHTIAQ, M; KHAN, SU; MOON, S; KHAN, MA; AHMAD, SS; AKBER, SS (Biological and Clinical Sciences Research Journal, 2023)
Since its discovery in December 2019, coronavirus disease-2019 (COVID-19) has become an increasingly serious global health concern due to its sharp rise in cases and fatalities. Since occupational therapy staff members are the initial line of defence against the COVID-19 epidemic , having sufficient knowledge, practise, and attitudes (KPA) about the disease may improve their capacity to prevent self-infection, lower mortality, and deliver quality medical care during the pandemic. This study aimed to evaluate the OT staff at RMI’s KPA toward COVID-19. This cross-sectional research was conducted at Rehman Medical Institute Peshawar using a questionnaire survey completed by OT staff members at various OTs. The research team physically distributed questionnaires. This 21-item survey is divided into four main sections to evaluate the respondents’ demographics, practises, and attitudes regarding COVID-19. In all, 178 people took part in the research. Most were women. Males made up 51% (n = 90) and 49% (n = 88). To establish the overall score, we computed the average of all correct answers given by participants to the knowledge section questions. 92 (51.6%) participants had a solid knowledge of COVID-19 symptoms and high-risk patients, while the remaining 86 (48.4%) had a rudimentary understanding of the disease. Similarly, 149 participants (83.7%) reported good practices, and 29 (16.3%) reported poor practices. 92 (51.6%) participants had a solid knowledge of COVID-19 symptoms and high-risk patients, while the remaining 86 (48.4%) had a rudimentary understanding of the disease. Furthermore, after being in contact with the patient and colleagues, some of them became concerned about returning home and infecting their family members. According to the findings, 111 (62.3%) of the participants had a positive attitude toward COVID-19 positive patients, while the remaining 67 (37.7%) had a negative attitude. As the worldwide COVID-19 danger develops, OT Staff from Rehman Medical Institute Peshawar exhibits acceptable KAP regarding COVID-19. There was a considerable gap in OT Staff expertise and attitude. During this epidemic, institution policymakers and OT staff should continue ongoing education, training, and follow-up updates.